THE EFFECT OF INFLATION AND EXCHANGE RATE ON THE SHARE PRICES OF TRANSPORTATION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Hasmirati Hasmirati; Alfin Akuba (Komitmen: Jurnal Ilmiah Manajemen, 2022)
This study aims to determine and analyze to what extent the effect of Inflation and Exchange Rates on share prices of transportation sub-sector companies listed on the Indonesia Stock Exchange. This study is a quantitative type of research method. The method of analysis employs multiple linear regression. The results of the study indicate that inflation and exchange rates simultaneously have no significant effect on the share prices in transportation sub-sector companies listed on the Indonesia Stock Exchange. The inflation value and exchange rate are projected with the Middle Exchange Rate to affect the share price of the transportation sub-sector. Partially, inflation has no significant effect on share prices. In general, inflation is a tendency to increase the price of goods continuously, it is caused by the amount of money circulating higher than the available goods and services. Partially, the exchange rate has no significant effect on share prices. There is no effect of the Exchange Rate on share prices in transportation sub-sector companies because the movement of the Rupiah exchange rate against foreign currencies (dollars) is not too significant.